Effects of Oxidation-Reduction Potentials on Soil Microbes - Dayo-Olagbende, Gabriel Olufemi; Adejoro, Solomon Alaba; Ewulo, Babatunde Sunday; Awodun, Moses Adeyemi (Agricultura Scientia, 2020)
Soil microbes are important in various processes that lead to soil fertility, nutrient availability and plant nutrition. These soil microbial organisms are themselves affected by the environment where they occur. Microbes could either be aerobic or anaerobic depending on their oxygen requirements. Oxidation-reduction reaction is a common reaction in anoxic environments and microbes tend to respond to it in different ways. This study therefore sets out to investigate the effect of oxidation-reduction potentials of the soil on activities of soil microorganisms. Results from this study show that highly reduced soils favors bacteria population more than fungi. It was concluded that the survival of fungi is best supported under oxidized and moderately reduced soils, but their existence can be negatively affected when soils become highly reduced. Bacteria that are aerobic thrive best under oxidized and moderately reduced soil. In these conditions, the highest microbial respiration in the soil was also measured.